Los valores educativos del deporte: el fair-play como ética cívica / The educational values of sport: fair-play as a civic ethic - CHIVA-BARTOLL, Oscar (Utopía y Praxis Latinoamericana, 2019)
RESUMEN Este trabajo presenta, desde un interés educativo, una interpretación de la ética del deporte entendida como concreción de la ética cívica aplicada al hecho deportivo. Al analizar el origen de los valores educativos del deporte se concluye que éstos se agrupan en torno a dos grandes polos: valores intrínsecos referidos a su dimensión práctica y valores extrínsecos relativos a la esfera social. El texto argumenta que, atendiendo principalmente a los valores extrínsecos, estos no pueden ser sino entendidos como una concreción de los principios morales dominantes por la sociedad que vio nacer al deporte moderno: la ética cívica. ABSTRACT This text presents, from an educational aim, an interpretation of the sport ethics understood as concretion of the civic ethics applied to the sporting event. When analysing the origin of sport educational values, we conclude that these are grouped around two major poles: intrinsic values related to their practical dimension and extrinsic values related to its social sphere. This paper argues that, when it refers to the field of external values from the social context, these can only be understood as a concretion of the moral principles dominated by the society that gave birth to modern sport: the civic ethics.